Isolation, characterization, and sequence of an Escherichia coli heat shock gene, htpX. - Kornitzer, D (1991)
We isolated and characterized a new Escherichia coli gene, htpX. The htpX gene has been localized at min 40.3 on the chromosome. We determined its transcription and translation start site. htpX expresses a 32-kDa protein from a monocistronic transcript; expression of this protein is induced by temperature upshift. htpX is expressed from a sigma 32-dependent promoter and is thus part of the heat shock regulon. Cells carrying a htpX gene disruption grow well at all temperatures and under all conditions tested and have no apparent phenotype. However, cells which overexpress a truncated form of the protein display a higher rate of degradation of puromycyl peptides.